The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cryst11070838
|View full text |Cite
|
Sign up to set email alerts
|

Modern History of Organic Conductors: An Overview

Abstract: This short review article provides the reader with a summary of the history of organic conductors. To retain a neutral and objective point of view regarding the history, background, novelty, and details of each research subject within this field, a thousand references have been cited with full titles and arranged in chronological order. Among the research conducted over ~70 years, topics from the last two decades are discussed in more detail than the rest. Unlike other papers in this issue, this review will he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 949 publications
(446 reference statements)
0
18
0
Order By: Relevance
“…30) Note that single-crystal X-ray structural analyses revealed that all the inner four chalcogen atoms in Fig. 1(a) possess equal electron densities; 28,35) thus, all the electron densities are obtained by averaging all the inner chalcogen atoms, suggesting a delocalized wave function. Instead of the previous localized wave functions of patterns 1 and 2, our new method provides a delocalized wave function, which is given by a linear combination of the patterns 1 and 2.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…30) Note that single-crystal X-ray structural analyses revealed that all the inner four chalcogen atoms in Fig. 1(a) possess equal electron densities; 28,35) thus, all the electron densities are obtained by averaging all the inner chalcogen atoms, suggesting a delocalized wave function. Instead of the previous localized wave functions of patterns 1 and 2, our new method provides a delocalized wave function, which is given by a linear combination of the patterns 1 and 2.…”
Section: Introductionmentioning
confidence: 98%
“…In Sect. 4, our calculation is compared with experimental results, 34,35) by choosing a reasonable magnitude of λ. Section 5 is devoted to a summary and comparison of the σ x /σ y of α-STF 2 I 3 with those of α-ET 2 I 3 and α-BETS 2 I 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the general molecular systems, the electronic structures including those under high pressure are calculated by DFT methods [10][11][12]. Although DESs were initially found in graphene [13,14] and some inorganic compounds [15], those found in organic compounds [16] possess clear advantages over their inorganic counterparts. For example, most organic DESs are found in bulk systems with well-defined crystal structures and chemical stoichiometries, whereas inorganic DESs often lack either of these two features.…”
Section: Introductionmentioning
confidence: 99%
“…Radical-cation salts and charge transfer complexes based on derivatives of tetrathiafulvalene (TTF) constitute a wide class of organic materials with transport properties ranging from insulating to superconducting [1][2][3][4]. This work is part of the systematic study of radical-cation salts of tetrathiafulvalene and its derivatives with metallacarborane anions, of which earlier results were summarized in works [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the compounds studied were BEDT-TTF-based radical-cation salts, recently, we have synthesized radical-cation salts based on such unconventional and rather exotic donors as bis (1,3-propylenedithio)tetrathiafulvalene [8,9], dibenzotetrathiafulvalene [10], and 4,5-ethylenedithio-4 ,5 -(2-oxa-1,3-propylenedithio)-tetrathiafulvalene [9]. On the other hand, although compounds of the composition (TMTXF) 2 Y (X = T, S) are usually classical organic metals among which the first organic superconductors were discovered [4,7], and TMTTF and TMTSF radical-cation salts continue to attract the attention of researchers [11][12][13][14][15], very little attention has been paid to TMTTF and TMTSF radical-cation salts with metallacarborane anions [16][17][18][19]. This prompted us to prepare and investigate new TMTTF and TMTSF radical-cation salts with metallacarborane anions.…”
Section: Introductionmentioning
confidence: 99%